Modifications Futsal Game Development to Learning Sport and Health Physical Education High School Students (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this research was to produce a product in the form of a modified futsal game model to learning material for futsal games in physical education subjects and the health at senior high school students (SMA). This research catergorized development research (Research and Development) to produce futsal game model products that are in accordance with the characteristics at senior high school students. This research was conducted at Kebumen 2 State Senior High School on April 4 to May 4, 2014 with a samples of 56 students from grade XI natural science 1 and grade XI sosial science 1. The method used in this research is the Borg and Gall model research with the stages: product analysis to be developed, product development, expert validation, product testing, and product revision. The results of the research based on data analysis note that the average percentage of data analysis from two squares is 90.5% with very good categorization, the average percentage of data analysis from Futsal experts is 88% with very good categories, the average percentage obtained from the small trial data is 90.16% with very good categories, the average percentage obtained from the analysis the data of the big test is 90.46% with very good categories. The conclusions of the results of the research that the game of modified futsal can be developed as a futsal game model that is in accordance with the characteristics at senior high school students and effective to be applied in learning futsal games.